A phenomenological-hermeneutic study exploring caring responsibility for a chronically ill, older parent with frailty - Helle Elisabeth Andersen; Bente Hoeck; Dorthe Susanne Nielsen; Jesper Ryg; Charlotte Delmar (Wiley, 2020)
Abstract Aim To provide lifeworld insights into experiences of adult children with caring responsibility for an 80+‐year‐old chronically ill parent with frailty. Background Informal care is common in Nordic welfare countries; however, little is known about adult children's experience of caring responsibility in this setting. Design A phenomenological-hermeneutic study based on Reflective Lifeworld Research. Methods Diaries and semi‐structured interviews with 12 adult children. Results Caring responsibility is identified as "a condition of life, filled with uncertainty." Three constituents contribute to this phenomenon: (a) balancing love, duty and reciprocity; (b) being the parent's advocate and manager; and (c) experiencing concerns and bodily strain. Conclusion Adult children work hard to provide care and enhance the well‐being of their parent. Heidegger's concept 'Fürsorge' may help us understand how by showing how caring responsibility means balancing different roles vis‐à‐vis the parent, one's own life and the health and social systems. Caring responsibility changes the relationship between parent and child.